Hippocalcin Is Required for Astrocytic Differentiation through Activation of Stat3 in Hippocampal Neural Precursor Cells - Kang, Min-Jeong; Park, Shin-Young; Han, Joong-Soo (Frontiers in Molecular Neuroscience, 2016)
Hippocalcin (Hpca) is a neuronal calcium sensor protein expressed in the mammalian brain. However, its function in neural stem/precursor cells has not yet been studied. Here, we clarify the function of Hpca in astrocytic differentiation in hippocampal neural precursor cells (HNPCs). When we overexpressed Hpca in HNPCs in the presence or absence of bFGF, expression levels of nerve-growth factors such as neurotrophin-3 (NT-3), neurotrophin-4/5 (NT-4/5) and brain-derived neurotrophic factor (BDNF), together with the proneural basic helix loop helix (bHLH) transcription factors neuroD and neurogenin 1 (ngn1), increased significantly. In addition, there was an increase in the number of cells expressing glial fibrillary acidic protein (GFAP), an astrocyte marker, and in dendrite outgrowth, indicating astrocytic differentiation of the HNPCs. Downregulation of Hpca by transfection with Hpca siRNA reduced expression of NT-3, NT-4/5, BDNF, neuroD and ngn1 as well as levels of GFAP protein. Furthermore, overexpression of Hpca increased the phosphorylation of STAT3 (Ser727), and this effect was abolished by treatment with a STAT3 inhibitor (S3I-201), suggesting that STAT3 (Ser727) activation is involved in Hpca-mediated astrocytic differentiation. As expected, treatment with Stat3 siRNA or STAT3 inhibitor caused a complete inhibition of astrogliogenesis induced by Hpca overexpression. Taken together, this is the first report to show that Hpca, acting through Stat3, has an important role in the expression of neurotrophins and proneural bHLH transcription factors, and that it is an essential regulator of astrocytic differentiation and dendrite outgrowth in HNPCs.